Translation Tests in The Assessment of Arabic Language Proficiency: A Theoretical and Practical Study Based on CEFR Levels: Tes Terjemahan dalam Penilaian Kemahiran Bahasa Arab: Kajian Teoretis dan Praktis Berdasarkan Tingkatan CEFR - Desal Putri Ramdhani; Ihwan Mahmudi; Amelda Dahni; Rizki Alifia Putri; Ratna Ayu; Tina ‘Ulwiana; Rifka Zakiatunnisa (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2026)
This study explores the role of translation tests in assessing Arabic language proficiency, with a theoretical foundation and practical implementation aligned with the Common European Framework of Reference for Languages (CEFR). The study adopts a descriptive-qualitative method using literature review and content analysis. The research instrument used was an analysis sheet for translation test items, developed from a synthesis of translation assessment models proposed by Newmark, Catford, and the CEFR, covering levels A1 to C2. The data were analyzed using content analysis techniques, including categorization, data reduction, cognitive-level mapping based on Bloom’s Taxonomy, and theoretical triangulation to ensure interpretive accuracy. These tests are mapped to Bloom’s Taxonomy to measure a spectrum of cognitive abilities from basic recall to creative synthesis. Results show that translation tests effectively evaluate key aspects of Arabic language proficiency, including comprehension of meaning, structural accuracy, cultural sensitivity, and both interpretive and productive abilities. At the A1–A2 levels, translation tests were used to assess learners’ ability to understand basic vocabulary and simple sentence structures, while at the B1–B2 levels, the tests assessed learners’ competence in interpreting contextual meanings, idiomatic expressions, and relationships between ideas. At the C1–C2 levels, translation tests demonstrated effectiveness in assessing analytical and evaluative skills, as well as the accurate reproduction of meaning in accordance with Arabic cultural and pragmatic contexts. Additionally, the study highlights four main evaluation methods: impressionistic, group, analytical, and mechanical to ensure valid and reliable scoring. The findings support the use of translation tests as a comprehensive tool for measuring communicative performance and language mastery in Arabic learning contexts. Keywords: Arabic Proficiency, Assessment, CEFR, Translation Pedagogy, Translation Test